The synergistic effect of retinyl propionate and hydroxypinacolone retinoate on skin aging - Wang, Qianqian; Hu, Fan; Hu, Xiaoyun; Xie, Yicheng; Du, Le; Ye, Rui (Journal of cosmetic dermatology, 2023)
Background Aging is responsible for the majority of skin and soft tissue remolding in humans. Retinol and its derivatives or retinoids effectively intervene skin aging process. Nevertheless, retinoids usually induce skin intolerance, especially among the Chinese, and thus, their application to prevent skin aging is yet to be well accepted. The study of optimal composition and concentration of retinoids is necessary to offer strong antiaging efficacies with minimum irritations. Therefore, a better understanding of retinol and its derivatives is acutely needed to develop strategies to combat skin aging. Objective In this study, we aimed to determine the optimal ratio of two retinol derivatives—hydroxypinacolone retinoate (HPR) and retinyl propionate (RP) in terms of dermal remodeling and skin aging prevention—and to investigate their synergistic antiaging effects both in vitro and in vivo. Methods An in vitro human foreskin fibroblast (HFF‐1) cell model was established to evaluate the cell viability of HPR and/or RP treatment. In addition, the antiaging and retinol receptor genes expressions in HFF‐1 cells cotreated with HPR and RP were quantified. The in vivo adverse reaction evaluation of skincare serums containing various levels of retinol or the optimal HPR and RP combination termed Gravi‐A was performed by 24 h patch tests in 33 subjects prior to the clinical research. Last but not the least, clinical research with 42 Chinese urban women was conducted to assess the in vivo antiaging efficacy of the skincare serum containing this optimal retinoid combination. Results The combination of HPR and RP at the weight ratio of 5:9 was shown to achieve the optimal in vitro antiaging performance. Coadministration of 5 μg/mL HPR and 9 μg/mL RP to HFF‐1 cells promoted their proliferation at 24 h and synergistically enhanced the expressions of type IV collagen, CRBP‐I, and RARB genes. In addition, the skincare serum containing HPR and RP combination at 5:9 weight ratio demonstrated superior in vivo anti‐wrinkle and skin elasticity improvement benefits without any adverse reactions, while retinol in the same concentration exerted much higher adverse effect. Skin wrinkles, skin smoothness, TEWL, skin elasticity R2 and R5 were improved by 8.3%, 11.9%, 25.7%, 14.5%, and 22.6%, respectively, after 8‐week use. Conclusion Our results indicated the advanced antiaging effect of HPR and RP combination both in vitro and in vivo. In addition, little adverse effect was observed in this study, in comparison with retinol. This combination named as Gravi‐A is a potential therapeutic strategy to prevent skin aging, especially for Chinese women.